2014
DOI: 10.9778/cmajo.20140011
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of prenatal alcohol exposure in Prince Edward Island: a population-based descriptive study

Abstract: Not all neonates exposed to heavy prenatal alcohol in utero will exhibit FASD; based on current estimates of predictive value for disease by exposure, our findings suggest that 1.3% of neonates born in PEI during this 1-year period will have FASD. In its application to an entire provincial birth cohort, this study successfully implemented a public health-centred approach for evaluating population-based risk of FASD, with implications for practice across Canada.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 33 publications
0
3
1
1
Order By: Relevance
“…The prevalence of positive FAEE analyses for significant prenatal alcohol exposure in our cohort was 2.5%. This is lower than the 3.1%–4.4% (39–56 of 1,271 samples) reported in the Prince Edward Island population-based study 36 with the greater observed maximum FAEE level than ours, and higher than the 2% (11 of 505 specimens) in a cohort of Southwestern Ugandan women with the maximum FAEE level similar to ours. 37 The relatively low prevalence in our cohort may result from sample collection in a low-risk community hospital setting, as opposed to high-risk settings such as special institutional clinics offering structured services.…”
Section: Discussioncontrasting
confidence: 87%
“…The prevalence of positive FAEE analyses for significant prenatal alcohol exposure in our cohort was 2.5%. This is lower than the 3.1%–4.4% (39–56 of 1,271 samples) reported in the Prince Edward Island population-based study 36 with the greater observed maximum FAEE level than ours, and higher than the 2% (11 of 505 specimens) in a cohort of Southwestern Ugandan women with the maximum FAEE level similar to ours. 37 The relatively low prevalence in our cohort may result from sample collection in a low-risk community hospital setting, as opposed to high-risk settings such as special institutional clinics offering structured services.…”
Section: Discussioncontrasting
confidence: 87%
“…This prevalence rate should be considered as an estimate of the true rate of heavy in utero alcohol exposure. As seen in a previous study focusing on a high-risk obstetric unit, the prevalence rate in this type of population is significantly higher than the general population 32 . As the MIREC study cohort has been shown to have a higher level of education and annual household income than the Canadian average, due to the voluntary nature of participation in the study, this estimate most likely refers to a higher SES portion of the Canadian population.…”
Section: Discussionmentioning
confidence: 49%
“…It also found that women are were unable to access legal abortion services turn to dangerous methods to self-induce, including excessive drinking, falling down stairs, and asking friends, family or partners to punch and kick their stomachs (MacQuarrie, MacDonald & Chambers, 2014). PEI has a relatively high incidence of Fetal Alcohol Syndrome, which may be connected to the number self-inducing methods involving alcohol and the use of these methods by women unable to access safe and legal abortions (Bryanton, Gareri, Boswall, McCarthy, Fraser, Walsh, Freeman, Koren, & Bigsby, 2014).…”
Section: History Of Abortion: Canada and Peimentioning
confidence: 99%